دعوة التقريب بين الأديان وموقف الإسلام منها: The Call for The Rapprochement of Religions and Islam’s Position on it - Rosmita; Mar’atu Shoaleha Lingga; Asnawati Patuti (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study examines the concept of the call for interfaith rapprochement (Da‘wah al-Taqrīb bayna al-Adyān) and the Islamic stance toward it through an analytical and critical approach based on the Qur’an, the Sunnah, and the statements of Muslim scholars. The significance of this research lies in revealing the true nature of this call and exposing its hidden motives, which aim to merge religions into a single faith and abolish the doctrinal distinctions that Allah has established between Islam and the distorted religions. The study seeks to answer several key questions: What is the reality of the call for interfaith rapprochement? What are its historical stages? What are its motives and impacts? And what is the Islamic ruling concerning it in light of Islamic creed? The researcher employed the inductive method by collecting relevant information from authentic sources and references, followed by analytical and critical examination. The study concludes that the call for interfaith rapprochement is a false and invalid concept that contradicts the fundamental principles of Islamic creed. It is founded on the notion of equating truth with falsehood and Islam with abrogated religions, and it poses serious threats to the faith and religious identity of Muslims.